Dose-Dependent Transient Decrease of Impedances by Deep Intracochlear Injection of Triamcinolone With a Cochlear Catheter Prior to Cochlear Implantation–1 Year Data - Prenzler, Nils K.; Salcher, Rolf; Lenarz, Thomas; Gaertner, Lutz; Warnecke, Athanasia (Frontiers in Neurology, 2020)
Administration of low-dose steroids via a catheter inserted into the cochlea to apply pharmaceuticals to more apical regions was previously shown not to be sufficient for long-term reduction of electrode impedances. The aim of the present study was to investigate the effect of intra-cochlear high-dose triamcinolone application on impedances in cochlear implant recipients. Patients received low-dose (4 mg/ml; n = 5) or high-dose (20 mg/ml; n = 5) triamcinolone via a cochlear catheter just prior to the insertion of a Med-El Flex28 electrode. Impedances were measured at defined time points from intra-operatively up to 12 months after first fitting and retrospectively compared with a control group (no steroid application). Patients who received a high-dose application of crystalloid triamcinolone showed significantly reduced impedances in the first fitting measurements compared to the control group. This effect was no longer detectable in patients of the low-dose group at that time. Looking at the different regions of the electrode, the impedance values were lowered significantly only at the basal and medial contacts. At later time points, there were no significant differences between any of the groups. This is the first study to demonstrate a dose-dependent reduction of impedances by deep intra-cochlear injection of triamcinolone in cochlear implant patients. With a high-dose, single application of triamcinolone using a cochlear catheter prior to insertion of a Flex28 electrode, the impedances can be significantly reduced up to and including the first fitting. Although the effect was longer lasting than when compared to low-dose triamcinolone, it was also not permanent.